Profile of Catheter-Related Infections in Hemodialysis Patients with Double Lumen Catheters at Dr. Reksodiwiryo Hospital, Padang - Mindy Pasuma Putra; Achmad Vidiansyah; Evelin Veronike; Harnavi Harun (Indonesian Journal of Kidney and Hypertension, 2025)
Background: Hemodialysis (HD) is the primary therapy for patients with advanced-stage chronic kidney disease (CKD). Although effective, the use of double lumen catheters (CDL) as vascular access in HD carries a high risk of infection. Objective: This study aims to identify the infection profile in CKD patients using CDL during hemodialysis at Dr. Reksodiwiryo Hospital in Padang. Methods: This study employs a retrospective descriptive design involving 60 hemodialysis patients from May to July 2024. The variables analyzed include age, gender, etiology, clinical manifestations, catheter location, catheter duration, and hematological parameters (leukocytes), with catheter-related infections (CRI) as the main dependent variable. Results: The results show that the majority of patients were under 60 years old (51.7%), and more than half (56.7%) used CDL for less than 8 weeks. CDL infections most frequently occurred in the right jugular vein access (90.0%) with fever and chills as the primary symptoms (53.3%). Conclusion: Using CDL for less than 8 weeks is linked to a high infection rate, with fever and chills as common symptoms. Recommendations include strict aseptic techniques during catheter insertion, prophylactic antibiotics for high leukocyte levels, and early planning for arteriovenous fistula (AVF) to minimize complications from long-term catheter use.